489 Complications Associated With Single Position Prone Lateral Lumbar Interbody Fusion: A Systematic Review and Meta-Analysis. (April 2023) - Farber, Samuel Harrison; Cecchi, Bayron Valenzuela; O'Neill, Luke; Chapple, Kristina; Zhou, James; Snyder, Laura A.; Turner, Jay D.; Uribe, Juan S.
Abstract : INTRODUCTION: Lateral lumbar interbody fusion (LLIF) is a workhorse surgical approach for lumbar arthrodesis. There is now emerging interest in performing single position surgery in which both LLIF and pedicle screw fixation are performed in the prone position. To date, most studies of prone LLIF are of poor quality and without long-term follow up; and as such, the complication profile related to this novel approach is not well known. METHODS: A systematic review of the literature and a meta-analysis were conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. All studies reporting prone LLIF were assessed for inclusion. Studies not reporting complication rates were excluded. RESULTS: A total of 10 studies met inclusion criteria and were included in the analysis. Overall, 286 patients were treated with prone LLIF across these studies with an average of 1.3 (0.2) levels per patient. There were 18 reported intra-operative complications including cage subsidence (3.8%), rupture of the anterior longitudinal ligament (ALL) (2.3%), cage repositioning (2.1%), aborted prone interbody placement (0.82%), and durotomy (0.6%). There were no reported major vascular or peritoneal injuries. A total of 68 post-operative complications occurred. These included thigh/groin sensory symptoms (13.3%), hip flexor weakness (17.8%), wound infection (1.9%), psoas hematoma (1.3%), motor neural injury (1.2%), and revision surgery (3.8%). CONCLUSIONS: Single position LLIF in the prone position appears to be a safe surgical approach with a low complication profile. Longer term follow up and prospective studies are needed in order to better characterize long-term complication rates related to this approach.